(untitled) (Journal of EAHIL, 2016)
The library of the Diaconia University of Applied Sciences (Diak) was invited to participate in a project “CapacityÂ Building in Crisis Preparedness in Health Care Education – CRIPS” funded by the Higher Education InstitutionsÂ Institutional Cooperation Instrument HEI ICI, Ministry for Foreign Affairs, Finland. The Diak LibraryÂ´s representative,Â Marketta Fredriksson, was named as one of the experts in the project. The paper describes her role and herÂ developmental work as an expert.